2011
DOI: 10.4097/kjae.2011.61.3.262
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic management in patients suspected of Creutzfeldt-Jakob disease -A case report-

Abstract: Creutzfeldt-Jakob disease (CJD) is a fatal neurodegenerative disorder in which accumulation of the pathogenic prion protein induces neuronal damage and results in distinct pathologic features. This abnormal prion is an infectious protein and resistant to methods of sterilization currently being used. Therefore, management of definite, or suspected CJD patients requires additional precautions. We report our experience of a patient who had undergone brain biopsy for suspected of CJD. The patient was confirmed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In another case report by McMurran et al, the authors also concluded with the same hypothesis of accelerated progression of CJD [5]. Similarly, it reflects that in this case report, there may be a sudden surge in systemic inflammatory mediators due to COVID infection, which might have led to the early demise of the patient despite our best efforts incorporating a multimodal approach consisting of remdesivir 100 mg, convalescent plasma therapy, methylprednisolone 62.5 mg, and LMWH 60 mg (0.6 ml) along with regular physical therapy, dietary, nutritional supplements, and standard ICU care as per the standard protocol [6][7][8].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In another case report by McMurran et al, the authors also concluded with the same hypothesis of accelerated progression of CJD [5]. Similarly, it reflects that in this case report, there may be a sudden surge in systemic inflammatory mediators due to COVID infection, which might have led to the early demise of the patient despite our best efforts incorporating a multimodal approach consisting of remdesivir 100 mg, convalescent plasma therapy, methylprednisolone 62.5 mg, and LMWH 60 mg (0.6 ml) along with regular physical therapy, dietary, nutritional supplements, and standard ICU care as per the standard protocol [6][7][8].…”
Section: Discussionmentioning
confidence: 90%
“…In such conditions, all necessary measures should be taken to substantially minimize the possibility of transmission between CJD patient and hospital worker and the number of staff in contact to be kept in minimal. Farling et al in a practical guide reported localization of small prions in equipment's microscopic crypts and their resistant nature to all sterilization techniques, including high dose ionizing radiation, ultraviolet radiation, and autoclaving [7]. In sCJD, along with COVID-19, we must advise remdesivir, plasma therapy, methylprednisolone, and LMWH.…”
Section: Discussionmentioning
confidence: 99%
“…Because of expected airway difficulties after extubation, fully monitored overnight surveillance in an isolated room was scheduled. Setup for anesthesia was prepared according to In's article [7]. Non-ferromagnetic standard monitoring (Precess, Invivivo Corp., Orlando, FL, USA) was connected.…”
Section: Anesthesiological Preparations and Proceduresmentioning
confidence: 99%
“…Cover all other equipment, the walls, the bed, and the floor of the working area with sheets of polyvinyl chloride (Figure 3). 59,60 Another neuroscience center has used disposable liquid‐repellent sheets (eg, surgical drapes and heavy‐duty surgical table covers) to achieve the same goal.These efforts have been shown to facilitate relatively easy disposal of potentially contaminated material 53 …”
Section: Perioperative Implicationsmentioning
confidence: 99%